A lightweight and high efficiency battery charger for electric vehicles - Yue, Xi Tong (2015)
Commercialization of electric vehicles (EV) has become a general trend nowadays, which requires a lot of research work. This project aims to develop a battery charger for EVs which is also employed in an inductive power transfer (IPT) system, focusing on increasing the efficiency and achieving lightweight, by introducing a novel soft-switched full-bridge (FB) DC/DC converter with proposed asymmetrical pulse width modulation (APWM) technique. The operating frequency is designed as 100 kHZ, and the size of transformer and inductor is reduced by using such a high frequency. This DC/DC converter achieves robust operation with soft-switching under a wide load range by employing an auxiliary circuit. This auxiliary circuit reactive current is achieved so that zero-voltage switching is guaranteed. Besides, voltage spikes across the output diode bridge of FB converter are eliminated by using two clamp diodes in the circuit, which leads to lower power loss and lower rating of the diodes and output filter capacitor. This project has two stages; the first stage is to design and develop a conventional FB converter with proposed APWM technique, and the second stage is to design and develop the newly proposed APWM converter. In this report, the operation of the newly proposed converter with APWM is presented, followed by design considerations. Simulation results for both converters are presented to verify the theoretical analysis. Moreover, a 100kHz, 1kW conventional FB DC/DC converter prototype with APWM is developed with experimental results.